Clinical predictive biomarkers for normoalbuminuric diabetic kidney disease. (July 2018) - Gohda, Tomohito; Nishizaki, Yuji; Murakoshi, Maki; Nojiri, Shuko; Yanagisawa, Naotake; Shibata, Terumi; Yamashita, Mami; Tanaka, Kanako; Yamashita, Yoshinori; Suzuki, Yusuke; Kamei, Nozomu
Abstract: Aims: A portion of patients with diabetes mellitus follow the progression of a non-albuminuria-based pathway; i.e., normoalbuminuric diabetic kidney disease (NA-DKD). However, the risk factors which determine NA-DKD are not yet fully understood. This cross-sectional study was therefore aimed to investigate the association between various biomarker levels and estimated glomerular filtration rate (eGFR) in patients with type 2 diabetes mellitus and normoalbuminuria (T2D-NA). Methods: We measured cardiovascular disease (CVD) [serum osteoprotegerin (OPG), plasma brain natriuretic peptide (BNP), cardio-ankle vascular index (CAVI)], tubular damage [urinary L-type fatty acid binding protein (L-FABP)], and inflammatory [serum tumor necrosis factor (TNF) α and its receptors (TNFRs)] biomarkers in 314 patients with T2D-NA. Results: The biomarkers of CVD and inflammation showed a significant negative correlation with eGFR. In a logistic multivariate model, none of the biomarkers, except TNFα and TNFRs, were associated with reduced renal function (eGFR < 60 mL/min/1.73 m 2 ) after adjustment for possible biological and clinical covariates. However, the association observed in TNFα was lost after adjusting for TNFR and other covariates. Conclusions: In patients with T2D-NA, elevated levels of circulating TNFRs, but not of TNFα, were strongly associated with reduced renal function, independently of all relevant covariates.